The role of the expanded food and nutrition education program in improving healthy eating index scores for low-income households in selected counties in Texas. - Oral Capps; Xingguo Wang (PLoS ONE)
The Expanded Food and Nutrition Education Program (EFNEP) is a federal initiative aimed at improving the dietary behaviors and nutrition knowledge of low-income households. This study evaluates the impact of Texas EFNEP on the dietary quality of participants using data from across ten counties over four fiscal years (2019-2022). Dietary quality was assessed using the Healthy Eating Index-2015 (HEI), calculated from 24-hour dietary recalls collected before and after participation in the program. The study analyzed changes of HEI scores across fiscal years, counties, socio-demographic characteristics, and public assistance program participation. The Texas EFNEP intervention resulted in a statistically significant improvement in overall HEI scores, 4.23 on average. The greatest dietary improvements were noted in Tarrant and Hidalgo counties. Among racial groups, participants identified as Asian showed the most improvement on average, followed by participants identified as white and as black. On average, Hispanic participants experienced greater dietary improvements than non-Hispanic participants. Based on regression analysis, geographic location and participation in public assistance programs such as the Child Nutrition Program (CNP) significantly impacted total HEI scores, but age, income, and hours taught in EFNEP were not statistically significant determinants. Statistically significant improvements were detected in eight of the nine adequacy components of the HEI, including total fruit, whole grains, and dairy. Concerning the moderation components, statistically significant changes were evident for refined grains, added sugar, and saturated fat. However, the program was less effective in moderating sodium intake, a known dietary challenge in low-income populations. The findings suggest that the Texas EFNEP contributed to improvements in overall dietary quality, including enhancements in both adequacy and moderation components of the Healthy Eating Index. These findings are consistent with prior research concerning the effectiveness of EFNEP studied in other states and regions.